2019
DOI: 10.1177/0093650219838959
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Violating the 180-Degree Rule on Film Viewing Preferences

Abstract: The 180-degree rule is thought to help smooth the change between film shots. When two individuals are speaking to each other, there is an imaginary axis of action running between them. If the camera crosses this axis, it breaks the 180-degree rule. A violation of the 180-degree rule is thought to have negative effects on viewers’ enjoyment of films. The present study investigated this idea. Experiment 1 established that naive participants can detect violations in videos. Experiment 2 tested the putative negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This may be due to the greater immersion and information brought about by the VR environment, with participants needing to exert more effort to process the content of the film clips. For the different edit types of 2D videos, Kachkovski et al [2] proved that cross-axis editing can lead to confusion and disorientation for viewers, but does not affect the viewers' enjoyment. The results of the NASA-TLX scale showed that this conclusion applies not only in 2D display mode but also in VR display mode; for the performance subscale, scores were similar between edit types.…”
Section: Subjective Ratingmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the greater immersion and information brought about by the VR environment, with participants needing to exert more effort to process the content of the film clips. For the different edit types of 2D videos, Kachkovski et al [2] proved that cross-axis editing can lead to confusion and disorientation for viewers, but does not affect the viewers' enjoyment. The results of the NASA-TLX scale showed that this conclusion applies not only in 2D display mode but also in VR display mode; for the performance subscale, scores were similar between edit types.…”
Section: Subjective Ratingmentioning
confidence: 99%
“…For the shot editing of dialogue scenes, the audience needs to understand the relationship between the actors' positions. Continuity editing follows a basic scheduling rule, the "axis rule", or the 180-degree rule [2]. The so-called axis refers to a virtual straight line formed between the subject's direction of vision, the direction of motion, and the object of communication with it.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that the clip stimuli mainly responded to the higher cognitive areas, which could be the further processing of cognitive and visual information at the cognitive level, thus responding to the visual cortical areas of the human brain. For the trans-axial behavior of traditional images, George et al demonstrated that this editing technique would confuse and disorient the viewer [5] but would not change the viewer's enjoyment of the images. The NASA-TLX results show that C0 provides the least load perception and is statistically different from C2-1, C2-2, C3-30, and C3-108.…”
Section: Vep Sources Analysismentioning
confidence: 99%
“…According to the theory of cognitive event segmentation, editing connects clips shot at different times and places. Although the visual content might change dramatically according to different editing methods, viewers can effortlessly perceive the discontinuous flow of information as a series of coherent events [4], e.g., the 180-degree rule [5], which may smooth out the changes between scenes, and whose violation can cause confusion and discontent among the audience. However, the emergence and development of VR films have subverted and reconstructed traditional film narrative modes.…”
Section: Introductionmentioning
confidence: 99%